Structural basis of the auto-inhibition mechanism of nonreceptor tyrosine kinase PTK6 - Ko, Sunggeon; Ahn, Kyo-Eun; Lee, Young-Min; Ahn, Hee-Chul; Lee, Weontae (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2009)
Protein tyrosine kinase 6 (PTK6) is composed of SH3, SH2, and Kinase domains, with a linker region (Linker) between the SH2 and Kinase domains. Here, we report the structural basis of the SH3-Linker interaction that results in auto-inhibition of PTK6. The solution structures of the SH3 domain and SH3/Linker complex were determined by NMR spectroscopy. The structure of the SH3 domain forms a conventional beta-barrel with two beta-sheets comprised of five beta-strands. However, the molecular topology and charge distribution of PTK6-SH3 slightly differs from that of the other SH3 domains. The structure of the N-terminal Linker within the complex showed that the proline-rich region (P175-P187) of the Linker forms a compact hairpin structure through hydrophobic interactions. The structure of the SH3/Linker complex revealed intra-molecular interaction between the amino acid pairs R22/E190, W44/W184, N65/P177, and Y66/P179. Mutations in PTK6 at R22,W44, N65, and Y66 residues in the SH3 domain increased catalytic activity compared with wild-type protein, implying that specific interactions between hydrophobic residues in the proline-rich linker region and hydrophobic residues in the SH3 domain are mainly responsible for down-regulating the catalytic activity of PTK6. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: SH2-KINASE LINKER; NMR-SPECTROSCOPY; SH3 DOMAIN; BRK; EXPRESSION; PROGRAM; FAMILY; TUMORS